Transaction Cost Economics Identification in Malaysian Housing Development: A Preliminary Review - Zainuddin, Farah Kamilah; Mustapa, Muzani; Mustapa, Fara Diva (International Journal of Sustainable Construction Engineering and Technology, 2021)
Shelter, albeit being one of the crucial physiological needs in Maslow’s Hierarchy of Needs, is still considered as luxury needs as many people still struggle to afford a house especially in Malaysia. The issue stemmed from the mismatch between the affordability level and the housing prices. Many research delved from the demand and supply perspective to find the root cause, however, the problem still prevails. Hence, this research aimed to study the aforementioned issue from the transaction cost economics (TCE)’s perspective. TCE provides a platform to allow parties to deduce the invisible costs from transaction of activities. This can be done by determining the effectiveness of each transaction profile by enhancing the value between the two transactions, hence, lower the costs. This paper outlined a preliminary finding on TCE’s identification in typical housing development process based on RIBA Plan of Work 2013 process protocol. RIBA Plan of Work 2013 was chosen to provide a standard platform of measurement to ensure consistency in activities listed in the pre-contract and post-contract in typical housing development process. Interviews were conducted with purposive sampling with individuals working directly with housing development. The respondents were asked to verify the list of pre-determined TCEs by indicating whether those activities constitute under the TCEs components and whether activities identified as redundant or inefficient can be removed or enhanced. Analysis conducted using the frequency analysis managed to determine the most important and also the most redundant transaction cost components in a typical housing development. The findings revealed an interesting fact where the number of transaction cost components at both pre and post-contract were higher than the anticipated number attained from literature review. Higher number of identified transaction cost components indicates higher transaction cost in housing development. This further suggested that certain activities which were found redundant or inefficient can be either removed or enhanced to lower the transaction costs. The research findings provide a useful platform to further verify the TCE in housing development. The components will be quantified to ultimately develop a framework for a best practice transaction cost economics model to apprehend unaffordable housing issues. Hence, it is noteworthy that combining TCE and Lean Management theory will enhance this on-going research on identification and quantification of the transaction costs within the housing development to address matters that cause high transaction costs that subsequently increases the housing prices.